Proceedings of the 9th International Conference on Fracture Mechanics of Concrete and Concrete Structures 2016
DOI: 10.21012/fc9.219
|View full text |Cite
|
Sign up to set email alerts
|

The use of Ultra High Performance Fibre Reinforced cement-based Composites in rehabilitation projects: a review

Abstract: Ultra High Performance Fibre Reinforced cement-based Composites (UHPFRC) form a novel material developed over the last two decades. A set of special traits, such as durability, outstanding material properties, and ease of application, render UHPFRC particularly attractive for the improvement (rehabilitation, strengthening) of concrete structures. Laboratory tests indicate a compressive strength, which ranges from 150 to 200 MPa, while tensile strength lies in the range of 7-15 MPa. The fibres play an important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 29 publications
0
10
0
2
Order By: Relevance
“…Hence, it is crucial to develop novel concepts for the strengthening of concrete structures. Martín-Sanz, Chatzi, and Brühwiler (2016) reported that promising is the applicability of UHPFRC at increased slopes, delivering satisfactory results which permits rehabilitation of surfaces that are not easily accessible by other means. Lampropoulos, Paschalis, Tsioulou, and Dritsos (2016) observed superior performance for beams strengthened with UHPFRC three side jackets, and the shrinkage strain was 30% reduced in case of UHPFRC with 3% steel fibres, compared to the respective measurements of plain UHPFRC.…”
Section: Mechanical Properties Of Ultra High Performance Fibre Reinforced Concrete: Flexural Characteristics Of Ultra High Performance Fimentioning
confidence: 99%
“…Hence, it is crucial to develop novel concepts for the strengthening of concrete structures. Martín-Sanz, Chatzi, and Brühwiler (2016) reported that promising is the applicability of UHPFRC at increased slopes, delivering satisfactory results which permits rehabilitation of surfaces that are not easily accessible by other means. Lampropoulos, Paschalis, Tsioulou, and Dritsos (2016) observed superior performance for beams strengthened with UHPFRC three side jackets, and the shrinkage strain was 30% reduced in case of UHPFRC with 3% steel fibres, compared to the respective measurements of plain UHPFRC.…”
Section: Mechanical Properties Of Ultra High Performance Fibre Reinforced Concrete: Flexural Characteristics Of Ultra High Performance Fimentioning
confidence: 99%
“…Most of these studies were focused on the material properties, and only few addressed the behaviour of structural UHPC members. In this latter group of studies is included the work by Bruwhiler et al, developed at EPFL, which uses UHPC to improve the performance of both existing and new concrete structures [42,43].…”
Section: Structures With Ultra-high Durability Concrete Covermentioning
confidence: 99%
“…El comportamiento mecánico bajo pruebas de tracción directa del UHPFRC puede clasificarse como ''ablandamiento por deformación'' o ''endurecimiento por deformación'' [24,25]. El efecto de las fibras cosiendo la fisura generada afecta significativamente al rendimiento en el dominio de endurecimiento y ablandamiento [26]. Según Naaman y Reinhart [27], el endurecimiento por deformación se produce cuando el esfuerzo a la tracción máximo posterior la fisuración de la matriz (σ pc) excede la resistencia a la tracción que produce la aparición de la primera fisura en el concreto (σcc).…”
Section: Introductionunclassified